Encapsulated Cardamom Waste Extract (Amomum compactum) Supplementation Improves Health and Performance of Broiler Chickens - Alfonia, R.; Ismadi, V. D. Y. B.; Sugiharto; Krismiyanto, L. (Faculty of Animal Science, IPB University, 2026)
Encapsulated cardamom waste extract (ECWE) contains flavonoids with antibacterial and antioxidant properties that may enhance broiler health and performance. This study evaluated the effects of ECWE as a phytobiotic on broiler intestinal microbiota, pH, H/L ratio, lymphoid organs, and performance. A total of 200 unsexed Ross broilers (8 days old) with an average body weight of 215.08±5.1 g/bird were assigned to five dietary treatments: T0 (control), T1 (0.02% ECWE), T2 (0.04% ECWE), T3 (0.06% ECWE), and T4 (0.08% ECWE). Results showed that 0.08% ECWE significantly increased lactic acid bacteria (LAB) populations, lymphoid organ, and broiler performance. The increase in LAB given 0.08% ECWE is more effective in helping to reduce intestinal pH and to minimize the growth of pathogenic bacteria that can interfere with chicken digestion. In addition, the antioxidant properties in ECWE had a positive effect on the development of lymphoid organs, especially the thymus. It is concluded that ECWE supplementation at 0.08% was the most effective in improving digestive tract health and optimizing broiler performance.